The Impact and Spatial Spillover Effect of the Digital Economy in the Yangtze River Delta on the Income Gap between Urban and Rural Residents - Xu, Yunqing; Li, Dongsheng (International Journal of Global Economics and Management, 2024)
At present, with the rapid development of the digital economy, the issue of the income gap between urban and rural areas has drawn much attention. Based on the panel data of 41 cities in the Yangtze River Delta region from 2011 to 2022, this paper conducts a benchmark regression and finds that the development of the digital economy has a "U-shaped" impact on the income gap between urban and rural residents. Subsequently, by establishing a spatial econometric model, it is discovered that there exists a significant inverted "U-shaped" spatial spillover effect of the digital economy on the income gap between urban and rural residents. Therefore, full consideration should be given to regional differences, the process of new urbanization should be continuously promoted, the integrated development of urban and rural areas and the coordinated development of regions should be vigorously advanced to realize the integration of the Yangtze River Delta, thereby creating more favorable conditions and opportunities for narrowing the income gap between urban and rural areas.